Rolling contact fatigue resistance of PVD CrN and TiN coated austempered ductile iron - Colombo, Diego Alejandro (2013)
This work studies the rolling contact fatigue (RCF) behavior of PVD CrN and TiN coated ADI samples. The effect of the substrate surface finishing method (grinding and polishing) and coating material on RCF life is also evaluated. Coatings were applied in an industrial reactor. Deposition times were adjusted to obtain similar coating thicknesses in both coating materials. RCF tests were performed in a flat washer type testing rig, using a thrust ball bearing as a counterpart. The maximum contact pressure (p0) was set at 1000 and 1400 MPa. The results obtained indicate that the RCF tests performed at p0=1000 MPa cause no failures on the samples analyzed, while those performed at p0=1400 MPa cause failures in both uncoated and coated samples. Failures in coated samples are mainly characterized by coating delamination and, to a lesser extent, by spall formation in the substrate. Graphite nodules present on the substrate surface act as preferential sites for coating fracture and subsequent delamination. The RCF resistance of coated samples is lower than that of uncoated samples regardless of the substrate surface finishing method employed. The surface hardening produced by the abrasive cutting of grinding improves the RCF resistance of the uncoated and coated samples.